Glacial Hazards and Avalanches in High Mountains of Nepal Himalaya (Journal of Tourism and Himalayan Adventures, 2020)
This paper provides a comprehensive overview of the glacial hazards (GHs) and reflects the situations in the Nepal Himalaya. We discuss on the different GHs with focus on the avalanches (snow, ice, and rock), presenting a nationwide database on avalanches compiled from literature. We also share the relevant policies in the GHs and lays groundwork for future research on the high-altitude hazards. GHs are prone to high mountains of Nepal, yet it is startling that the area has received the least priority. Almost every year, human casualties and property losses reported due to various disastrous events in the country. We documented 60 avalanche events since the 1920s across the country, ensuing the loss of more than 370 human lives. Almost all high-altitude regions of Nepal are prone to avalanches. Number of avalanche events and casualties were the highest in the Khumbu region of Nepal. In recent years, the avalanche records and casualties are also expanding in other parts of the country, most likely due to increased human activities at high altitude regions and documentation. It is inevitable to analyze the hazards prevalent in the mountains to ensure safe and secure livelihood, trekking, and mountaineering activities. We also underline the urgent research priorities to provide a more systematic understanding of GHs in Nepal.